Controversy of the Capability of Voters with Mental Health Disorder in the General Election (Medico Legal Update, 2020)
In the Republic of Indonesia’s Constitution, Article 22E paragraph (1), it is stated that the execution of thegeneral election must be done in a manner which is direct, general, libre, confidential, honest and fair. Everycitizen has a right which is guaranteed constitutionally to participate in the general election including thosewho are mentally disabled.They have the right to freely participate both directly or by electing the representatives who will be inthe government. Historically, the prohibition of the voting rights for mentally disabled people is not inaccordance with the Human Rights except with clear circumsance.